Design Solutions for a Low-Power SoC Platform Using Near-Threshold Voltages - Mika Kutila; Marko Ylitolva; Jonas Eriksson (My University, 2025)
In the future the number of small sensor-based devices is going to increase. The Internet-of-Everything (IoE) vision brings smart miniature electronic devices to objects surrounding our everyday lives. These devices are going to monitor our environment or ourselves. They are also going to execute small tasks based on their observations. Operations of this kind can be done with small low-performance devices. In this paper we present building blocks for a low-power system for sensor-based applications. Our work is aiming for reliable operation with supply voltage of 0.5 V instead of the nominal of 1.2 V. We describe low-power solutions used in 130 nm CMOS technology microprocessor, memory and clock generator. Depending on the component, we have managed to achieve reliable operation with voltages of 0.5-0.8 V. Power consumption of components reduce significantly when operating voltage is scaled down to near-threshold region.
Nordic microelectronics conference, NORCHIP 2014